2019
DOI: 10.1007/s40097-019-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ni base nanoparticles by W/O emulsion combustion

Abstract: To develop a process of fine particle production by spray pyrolysis, spray combustion of W/O (water-in-oil) emulsion, of which water phase was raw material solution and oil phase was fuel for heat source of high-temperature reaction field, was investigated. In this study, nickel oxide particles, which were a preliminary step of the nickel fine particle production, were synthesized and its structural characteristics were evaluated. Mixed solution of nickel nitrate and white kerosene was used as raw material. W/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Nano lubricants are a solution to this challenge and have received much attention in recent years; studies have indicated that adding small amounts of nano additives (about 0.2–2%) to the base fluid can improve its tribological properties 4 7 . Various types of nanoparticles, such as carbon-based materials (including carbon nanotubes and graphene nanoparticles) 8 10 , metal oxides (including titanium dioxide, cobalt oxide, zinc oxide, and iron oxide nanoparticles) 11 13 , and metals (including Al, Cu, Fe, Ni, and Ag), have been used as additives 14 16 . The nanoparticles have unique features due to their high specific surface area and smaller size than other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nano lubricants are a solution to this challenge and have received much attention in recent years; studies have indicated that adding small amounts of nano additives (about 0.2–2%) to the base fluid can improve its tribological properties 4 7 . Various types of nanoparticles, such as carbon-based materials (including carbon nanotubes and graphene nanoparticles) 8 10 , metal oxides (including titanium dioxide, cobalt oxide, zinc oxide, and iron oxide nanoparticles) 11 13 , and metals (including Al, Cu, Fe, Ni, and Ag), have been used as additives 14 16 . The nanoparticles have unique features due to their high specific surface area and smaller size than other materials.…”
Section: Introductionmentioning
confidence: 99%